2019
DOI: 10.1002/met.1799
|View full text |Cite
|
Sign up to set email alerts
|

Squall‐line initiation over the northern coast of Brazil in March: Observational features

Abstract: The daily cycle of atmospheric conditions related to squall‐line (SL) initiation over the northern coast of Brazil (NCB) was obtained for a specific month (March) over the course of a decade (2004–2013). March falls during the NCB's rainy season. A comparison of atmospheric conditions between two categories, the most intense SL events (SLC+) and the weakest coastal convection events (CC–), was carried out. For both categories, the daily cycle of convective cluster properties (i.e. number and area) over the NCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Since R6 has a large coastal strip, sea breezes in the region are frequent [1]. Under these conditions, the sea breeze transports moisture to the R6 inland, which interacts with the trade winds producing squall lines that enter the continent [1,[215][216][217]. Squall lines are MCSs that begin their formation north of the R6 in the late afternoon or early evening when convective cells agglomerate, forming a linear band of clouds parallel to the coast [216].…”
Section: Cluster 5-region 5 (R5)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since R6 has a large coastal strip, sea breezes in the region are frequent [1]. Under these conditions, the sea breeze transports moisture to the R6 inland, which interacts with the trade winds producing squall lines that enter the continent [1,[215][216][217]. Squall lines are MCSs that begin their formation north of the R6 in the late afternoon or early evening when convective cells agglomerate, forming a linear band of clouds parallel to the coast [216].…”
Section: Cluster 5-region 5 (R5)mentioning
confidence: 99%
“…Under these conditions, the sea breeze transports moisture to the R6 inland, which interacts with the trade winds producing squall lines that enter the continent [1,[215][216][217]. Squall lines are MCSs that begin their formation north of the R6 in the late afternoon or early evening when convective cells agglomerate, forming a linear band of clouds parallel to the coast [216]. Squall lines occur all year round but have a maximum frequency in the autumn when ITCZ reaches its southernmost position, directly affecting the instability conditions in the northern R6 [216].…”
Section: Cluster 5-region 5 (R5)mentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of precipitation in NEB is influenced by the different systems which occur in the region, such as the Intertropical Convergence Zone (ITCZ; Uvo, 1989;Utida et al, 2019); South Atlantic Convergence Zone (SACZ; Kodama, 1992;Zilli et al, 2019); Easterly Wave Disturbances (EWD; Torres and Ferreira, 2011;Gomes et al, 2019); Upper Tropospheric Cyclonic Vortex (Kousky and Gan, 1981;Fedorova et al, 2016) and Squall Lines (Kousky, 1980;Oliveira and Oyama, 2019). In addition, it is influenced by the interannual variability of Pacific Ocean temperature, associated with the El Niño Southern Oscillation (Ropelewski and Halpert, 1987;Marengo et al, 2017), and to the interannual variability of Atlantic Ocean temperatures (Bombardi et al, 2014;Rodrigues et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Later, French and Parker (2012) focused on 21 MFBE cases in North America from 2006 to 2010, and the analyses showed that the merged bow echoes normally produced more severe weather than the nonmerged ones. Oliveira and Oyama (2020) demonstrated squall line formation over the northern coast of Brazil and pointed out that the convective merging process was responsible for the long‐lasting and more intense convective systems, and the moisture at 700 hPa was crucial for system evolution.…”
Section: Introductionmentioning
confidence: 99%